Effectiveness of Respiratory-gated Positron Emission Tomography/Computed Tomography for Radiotherapy Planning in Patients with Lung Carcinoma – A Systematic Review. Issue 4 (April 2018) - Frood, R.; Prestwich, R.; Tsoumpas, C.; Murray, P.; Franks, K.; Scarsbrook, A.
Abstract: Aims: A systematic review of the literature evaluating the clinical use of respiratory-gated (four-dimensional; 4D) fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) compared with non-gated (three-dimensional; 3D) PET/CT for radiotherapy planning in lung cancer. Materials and methods: A search of MEDLINE, Cochrane, Web of Science, SCOPUS andclinicaltrials.gov databases was undertaken for articles comparing 3D and 4D PET/CT tumour volume or 4D PET/CT for radiotherapy planning. PRISMA guidelines were followed. Results: Thirteen studies compared tumour volumes at 3D and 4D PET/CT; eight reported significantly smaller volumes (6.9–44.5%), three reported significantly larger volumes at 4D PET/CT (16–50%), one reported no significant difference and one reported mixed findings. Six studies, including two that reported differences in tumour volumes, compared target volumes or studied geographic misses. 4D PET/CT target volumes were significantly larger (19–40%) when compared with 3D PET/CT in all but one study, where they were smaller (3.8%). One study reported no significance in 4D PET/CT target volumes when compared with 4D CT, whereas another study reported significantly larger volumes (38.7%). Conclusion: The use of 4D PET/CT leads to differences in target volume delineation compared with 3D PET/CT. These differences vary depending upon technique and the clinical impact currently remains uncertain. Correlation of pretreatment target volumes generated at 3D and 4D PET/CT with postsurgical histology would be ideal but technically challenging. Evaluation of patient outcomes based on 3D versus 4D PET/CT derived treatment volumes warrants further investigation.